Digestive tract morphology of the Neotropical piscivorous fish Cichla kelberi(Perciformes: Cichlidae) introduced into an oligotrophic Brazilian reservoir - Alejandra Filippo Gonzalez Neves dos Santos (Revista de Biología Tropical, 2011)
Despite being one of the most well-known cichlid fish of importance to artisanal and sport fishing, and among the largest fishes in the Neotropics, data on digestive tract anatomy of peacock basses (Cichla spp.) are largely lacking, especially for non-native populations. in this paper, we describe for the first time the digestive tract morphology of Cichla kelberi, a voracious piscivore that was introduced in the 1950s into an oligotrophic and physically low-complex impoundment in Brazil. Peacock basses were collected between 1994 and 2002 in Lajes Reservoir, through gillnets (25 to 55mm mesh; 20-50x2m), seines (10x2.5m; 8.0mm mesh), cast nets and angling. All the fishes were kept on ice in the field and then transferred to the laboratory, where they were identified, measured, weighed and dissected for digestive tract analyses. The index of Relative importance-IRI was calculated for diet characterization while linear and non-linear regressions were performed to assess growth patterns of four morphological characters related to feeding (e.g. mouth width, mouth height, stomach length and intestine length) and the number of gill rakers during the C. kelberi ontogeny. Most digestive tract structures were directly related to the piscivorous diet of C. kelberi, indicating that peacock bass is a diurnal, bathypelagic and gape-size limited predator that feeds largely on shallow-water prey species within the littoral zone. Mouth width and height grew allometrically (b>1) with the size of peacock bass, broadening the size range in which prey can be eaten, but especially for predators smaller than ~400mm of total length. Differently, stomach and intestine lengths increased isometrically (b=1), which could constrain prey consumption for adult C. kelberi, especially those at advanced stages of gonadal maturation. The presence of longer-drawn, sharp and furcated gill rakers in C. kelberi may be related to increased prey retention in the resource-limited Lajes Reservoir, but further studies are necessary whether such features are randomly triggered by genetic or phenotypic anomalies, or effectively bring ecological advantages to the predator. In addition to contribute to improve the current biological knowledge on peacock basses, our results can be also useful to further comparisons on whether those morphological features related to feeding will change with transitions on prey consumption by C. kelberi and/or with the particular conditions of the invaded ecosystem. Rev. Biol. Trop. 59 (3): 1245-1255. Epub 2011 September 01. A pesar de ser uno de los peces cíclidos más conocidos por su importancia para la pesca artesanal y deportiva, y entre los más grandes peces en el Neotrópico, los datos sobre la anatomía del tracto digestivo de los pavones (Cichla spp.) están bastante deficientes, especialmente para las poblaciones no nativas. En este trabajo se describe por primera vez la morfología del tracto digestivo de Cichla kelberi, un piscívoro voraz que se introdujo en la década de 1950 en un embalse oligotrófico y físicamente de baja complejidad en Brasil. Los pavones se recogieron entre 1994 y 2002 en el embalse Lajes, con redes de enmalle (25 a 55mm de malla, 20-50x2m), redes de cerco (10x2.5m, 8.0mm de malla), atarrayas y pesca. Todos los peces se mantuvieron en hielo en el campo y luego fueron trasladados al laboratorio, donde fueron identificados, medidos, pesados y disectados para el análisis del tracto digestivo. El Índice de importancia Relativa, el IIR se calculó para la caracterización de la dieta, mientras que las regresiones lineales y no lineales se realizaron para evaluar los patrones de crecimiento de cuatro caracteres morfológicos relacionados con la alimentación (por ejemplo: ancho de la boca, altura de la boca, longitud del estómago y longitud del intestino) y el número de branquiespinas en la ontogenia en C. kelberi. La mayoría de las estructuras del tracto digestivo estaban directamente relacionadas con la dieta de los piscívoros C. kelberi, lo que indica que el pavón es un depredador diurno, batipelágico y limitado por el tamaño de la boca abierta ya que se alimenta en gran medida de presas en aguas poco profundas de la zona litoral. El ancho de la boca y la altura tuvieron un crecimiento alométrico (b>1) con el tamaño de pavones, y se amplió el rango de tamaño en el que las presas se pueden ser comidas, pero sobre todo para los depredadores menores de ~400mm de longitud total. A diferencia, las longitudes del estómago y el intestino aumentaron isométricamente (b=1), lo que podría limitar el consumo de presas para adultos de C. kelberi, especialmente aquellos en etapas avanzadas de la maduración gonadal. La presencia de branquiespinas marcadas, agudas y furcadas en C. kelberi puede estar relacionada con un incremento en la retención de presas en los recursos limitados del embalse Lajes, pero son necesarios más estudios si tales características son desencadenadas al azar por anomalías genéticas o fenotípicas, o efectivamente son una ventaja ecológica para el depredador. Además de contribuir con el mejoramiento del conocimiento biológico actual en los pavones, nuestros resultados también pueden ser útiles para estudiar si las características morfológicas relacionadas con la alimentación van a cambiar con las transiciones en el consumo de presas por C. kelberi y/o con las condiciones particulares del ecosistema invadido.